The Influence of Self-Efficacy and Work–Life Balance on Employee Performance: The Mediating Role of Job Satisfaction - Ziputri Srilanda; Asep Gunawan; Harry Safari Margapradja (Al-Qalam Institue, 2026)
This study aims to examine the effects of self-efficacy and work–life balance on employee performance, with job satisfaction serving as a mediating variable. A quantitative research design employing a survey method was adopted. Data were collected using a structured Likert-scale questionnaire from 209 employees and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS. The findings demonstrate that self-efficacy and work–life balance have positive and significant effects on job satisfaction. In addition, job satisfaction positively and significantly influences employee performance. The mediation analysis further confirms that job satisfaction significantly mediates the relationships between self-efficacy, work–life balance, and employee performance, indicating that employees with greater confidence in their abilities and a healthier balance between work and personal life tend to experience higher job satisfaction, which subsequently enhances their performance. These findings highlight the importance of fostering employees’ psychological resources and promoting supportive work environments to strengthen organizational outcomes. The study contributes to the human resource management literature by providing empirical evidence on the mechanism linking individual and organizational factors to employee performance and offers practical implications for designing effective strategies to improve employee well-being, satisfaction, and sustainable organizational performance.